RATIONALITY OF USING PNEUMATIC LOOSENERS OF VIBRATION ACTION ON PLOW BODIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In modern agriculture, more and more attention is paid to the problems of energy consumption during deep tillage operations. One of the ways to solve this problem is the use of vibrations to facilitate the work of working bodies and reduce the traction resistance of the unit in general. This paper presents one possible implementation of this idea for a plowing unit. The proposed design improvement in this study involves developing a mechanism to induce vibrations in plow bodies. The theoretical basis is the establishment of general laws governing the effect of vibrations on traction resistance. Ensuring vibrations is offered by installing additional pneumatic vibration dampers in the blades on each plough body. This idea is protected by the patent of Ukraine. In order to establish the effect of vibrations on traction resistance, the Goryachkin's rational formula. was adapted in the work. The effect of vibrations in this formula was accounted for by modifying specific parameters based on scientific research on their influence on the coefficient of friction (f₀) and specific traction resistance (K). The theoretical dependence of traction resistance on the speed of movement of the unit for a plough with and without the use of pneumatic looseners is presented in the work. The graphs indicate that the use of oscillating looseners reduces the traction resistance of the plow by 19...23% in the speed range of 0.5…2.5 m/s. The results of these studies are completely correlated with the data from other studies and can be used to clarify and improve methods of calculating vibratory plough.